A Facile and Green Method for the Synthesis of SFE Borosilicate Zeolite and Its Heteroatom‐Substituted Analogues with Promising Catalytic Performances. Issue 2 (20th November 2017) - Luo, Yi; Wang, Zhendong; Sun, Junliang; Wang, Yingying; Jin, Shaoqing; Zhang, Bin; Sun, Hongmin; Yang, Weimin
Abstract: Synthesis of SFE‐type borosilcate zeolite was successfully carried out using a commercially available low‐cost organic structure directing agent (OSDA) with ultra‐low OSDA and water contents within a short crystallization time. Heteroatom (Al, Ti, V, or Fe)‐substituted SFE‐type zeolite analogues were also directly synthesized for the first time. The obtained Al containing zeolites exhibited promising catalytic performances in the disproportionation of isopropylnaphthalene. Abstract : A facile and green procedure for the direct synthesis of B, Al, Ti, V or Fe incorporated SFE‐type zeolites using commercially available low‐cost 4‐dimethylaminopyridine as an organic structure‐directing agent (OSDA) was developed. SFE borosilicate zeolites with high yields were synthesized with ultra‐low OSDA and H2 O contents within a short period of time. Al containing SFE zeolites show promising catalytic performance in the disproportionation of isopropylnaphthalene.